2015
DOI: 10.1130/g36048.1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering framboidal pyrite biogenicity using nano-scale CNorg mapping

Abstract: Framboidal pyrite has been used as a paleo-redox proxy and a biomarker in ancient sediments, but the interpretation of pyrite framboids can be controversial, especially where later overgrowths have obscured primary textures. Here we show how nano-scale chemical mapping of organic carbon and nitrogen (CN org ) can detect relict framboids within Precambrian pyrite grains and determine their formation mechanism. Pyrite grains associated with an Ediacaran fossil Lagerstätte from Newfoundland (ca. 560 Ma) hold sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 24 publications
6
52
0
Order By: Relevance
“…Recent work by MacLean et al (2008) provides evidence for the formation of framboidal pyrite on organic templates within microbial biofilms (Wacey et al, 2014). The pyrites observed in Santa Barbara Basin sediments are therefore consistent with biologically induced pyrite mineralization in association with sulfate-reducing microbial communities.…”
Section: Pyrite Formation In Santa Barbara Basinmentioning
confidence: 64%
“…Recent work by MacLean et al (2008) provides evidence for the formation of framboidal pyrite on organic templates within microbial biofilms (Wacey et al, 2014). The pyrites observed in Santa Barbara Basin sediments are therefore consistent with biologically induced pyrite mineralization in association with sulfate-reducing microbial communities.…”
Section: Pyrite Formation In Santa Barbara Basinmentioning
confidence: 64%
“…Each pyrite crystal was enclosed by a nano-porous organic rim, all of which were similar to the framboids that occur in a matrix of bacteria and biopolymers in modern sediments (MacLean et al, 2008). This suggests that a structural and chemical environment is provided by biofilms for the growth of pyrite framboids (MacLean et al, 2008;Wacey et al, 2015). Most pyrite framboids or irregular clusters in the Lantian shales showed neither structures enclosed by OM nor an organic rim around individual crystals; rather, the 2D images showed them apparently floating on the nano-porous OM matrix.…”
Section: Pore Characteristics Shown By Fe-sem Observationmentioning
confidence: 91%
“…4a, c, e). A recent study of Ediacaran siltstone using both FIB-SEM imaging and nanoscale secondary ion mass spectrometry (NanoSIMS) mapping (Wacey et al, 2015) found clear evidence of pyrite framboids enclosed by almost spherical nano-porous OM zones. Each pyrite crystal was enclosed by a nano-porous organic rim, all of which were similar to the framboids that occur in a matrix of bacteria and biopolymers in modern sediments (MacLean et al, 2008).…”
Section: Pore Characteristics Shown By Fe-sem Observationmentioning
confidence: 99%
“…Opportunity exists to use nanoSIMS to address other outstanding issues in the mineralogy of compositionally-zoned minerals, trace element partitioning, and in mineral processing. In one innovative application of nanoSIMS, Wacey et al (2015) [98] have used nanoSIMS mapping of organic carbon and nitrogen in framboidal pyrite, elucidating mechanisms of framboid formation in terms of organic biofilms.…”
Section: Nanoscale Secondary Ion Mass Spectrometry (Nanosims)mentioning
confidence: 99%